(Ultra) High Pressure Homogenization Potential on the Shelf-Life and Functionality of Kiwifruit Juice - Patrignani, Francesca; Mannozzi, Cinzia; Tappi, Silvia; Tylewicz, Urszula; Pasini, Federica; Castellone, Vincenzo; Riciputi, Ylenia; Rocculi, Pietro; Romani, Santina; Caboni, Maria Fiorenza; Gardini, Fausto; Lanciotti, Rosalba; et al. (Frontiers in Microbiology, 2019)
The increasing competition within the food industry sector makes the requisite of innovation in processes and products essential, leading to focus the interest on the application of new processing technologies including high pressure homogenization (HPH) and ultra high pressure homogenization (UHPH). In this context, the present research aimed at evaluating the effects of two (ultra) high pressure homogenization treatments performed at 200 MPa for 2 and 3 cycles on quality and functionality of organic kiwifruit juice stored at three different temperature, i.e. 5, 15 and 25 °C. The results showed that only the treatment performed at 200 MPa for 3 cycles was able to significantly increase the shelf-life of organic kiwifruit juices when stored at refrigeration temperature, avoiding also phase separation that occurred in the sample treated at 0.1 MPa (control) after 20 days of refrigerated storage. The obtained data showed also that the highest applied pressure was able to increase some quality parameters of the juice such as viscosity and luminosity (L*) and increased the availability of total phenol content consequently enhancing the juice total antioxidant activity. The application of a treatment at 200 MPa for 3 cycles allowed to obtain a stable kiwifruit juice for more than 40 days under refrigerated storage. A challenge to implement this technology in food process as full alternative to thermal treatment could be represented by the adoption of pressure level up to 400 MPa followed by the packaging in aseptic conditions.